Uso do Balanced Scorecard (BSC) na medição de desempenho organizacinal de hospitais privados do Paraná - Silva, Juliana Moraes da (2016)
The hospital management has become one of the hardest challenges of administration due to the variety of assistance services provided to society, the difficulty of using tax incentives and budgetary limits. Therefore, the implementation of capable strategies, to improve the performance in that context of services, has become a necessity. Managers have been looking for management tools related to Management Control System (MCS) and performance measurement (MP). Aligned with is theme, this research aimed identify the existence of a connection between performance measurement using dimensions, use of management control system and satisfactory results in organizational performance (OP) at the administrative level hospitals in the state of Paraná. The study was conducted through a survey, in which the questionnaire was sent to 185 of Paraná state hospitals. They obtained 102 responses submitted to factor analysis statistical technique for grouping of variables factors and Pearson correlation analysis for verification of relations. The results obtained demonstrated the reliability of models and indicated that 61% of respondents hospitas have 50 beds and 58% of them have up to 100 employees; there is a moderate relation between the use of MP and the use of MCS. The relation between use of the MCS and the OP is also considered moderate; although there is a moderate relation between the use of financial MP and customers with financial OP, the research did not find evidence that supported the relationship of financial MP and clients with customer OP, internal and learning processes; with respect the relation between MP learning with the OP, it is weak, considered negligible. Some limitations as the perception of the respondent of controllership and the stratification of private hospitals in Paraná, make impossible the generalize of results to health institutions. However, it contributes to a possible application survey with respondentes of new prifile, and different types of establishments. Despite the limitations of a non-probabilistic sample, the database can be used for application of other statistical techniques.